Plasma Endocannabinoid Alterations in Individuals with Substance Use Disorder are Dependent on the “Mirror Effect” of Schizophrenia - Desfossés, Joelle; Stip, Emmanuel; Ait Bentaleb, Lahcen; Lipp, Olivier; Chiasson, Jean-Pierre; Furtos, Alexandra; Venne, Karine; Kouassi, Edouard; Potvin, Stephane (Frontiers in Psychiatry, 2012)
Schizophrenia is a complex psychiatric disorder strongly associated with substance use disorders. Theoretically, schizophrenia and SUD may share endocannabinoid alterations in the brain reward system. The main endocannabinoids, anandamide and 2-arachydonoylglycerol, are lipids which bind cannabinoid receptors. Oleylethanolamide (OEA), a fatty acid ethanolamide, binds peroxisome proliferator-activated receptors. The endocannabinoid system has been shown to be impaired in schizophrenia, and recently, our group has shown that schizophrenia patients with SUD have elevated peripheral levels of anandamide and OEA that do not normalize after 3-month treatment with quetiapine. Objective For comparative purposes, we aimed to measure endocannabinoids in non-psychosis substance abusers and non-abusing schizophrenia patients. Methods Using liquid chromatography and mass spectrometry, we measures plasma levels of anandamide and OEA in non-psychosis SUD patients, non-abusing schizophrenia patients and healthy controls. In an open-label manner, all patients received 12-week treatment with quetiapine. Results Anandamide and OEA were reduced in substance abusers without schizophrenia, relative to healthy controls (p<0.05). Both endocannabinoids were unchanged in non-abusing schizophrenia patients. After quetiapine, anandamide and OEA levels remained significantly reduced the SUD group (p<0.05). Discussion Taken together with results of our previous study performed in dual-diagnosis patients, our results suggest that peripheral anandamide and OEA levels are impaired in patients with SUD in opposite ways according to the presence or absence of schizophrenia. Endocannabinoid alterations did not change with treatment, suggesting that they are trait markers. Further studies are necessary to understand the role of endocannabinoids in substance abusers with and without schizophrenia and to examine therapeutic implications.